2017 Physics Education Research Conference Proceedings 2018
DOI: 10.1119/perc.2017.pr.073
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an introductory lab course on students’ understanding of measurement uncertainty

Abstract: Physics lab courses are an essential part of the physics undergraduate curriculum. Learning goals for these classes often include the ability to interpret measurements and uncertainties. The Physics Measurement Questionnaire (PMQ) is an established open-response survey that probes students' understanding of measurement uncertainty along three dimensions: data collection, data analysis, and data comparison. It classifies students' reasoning into point-like and set-like paradigms, with the set-like paradigm more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Therefor (sic) the value on the textbook should be better and more accurate." Similarly, few students in either cohort support their textbook judgment with Excludes uncertainty, which may be similar to research demonstrating the rarity of explicit point reasoning in other populations [7,8]. Table II.…”
Section: A Contextual Cues Affect Students' Judgmentssupporting
confidence: 69%
See 1 more Smart Citation
“…Therefor (sic) the value on the textbook should be better and more accurate." Similarly, few students in either cohort support their textbook judgment with Excludes uncertainty, which may be similar to research demonstrating the rarity of explicit point reasoning in other populations [7,8]. Table II.…”
Section: A Contextual Cues Affect Students' Judgmentssupporting
confidence: 69%
“…The Physics Measurement Questionnaire was specifically developed to probe these broad ways of reasoning about measurement [1][2][3]. Research with the questionnaire has demonstrated that many students tend toward presenting mixed reasoning-perhaps due to contextual cues-that includes elements from both point and set reasoning [1,2,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The statistically significant shift in Item 5 suggests that, distinct from the concepts themselves, students' views about measurement uncertainty were affected favorably by the transformation. Previous work has shown that students in the original course already show pre-post shifts towards such conceptial understanding [8,9]. Additional work is needed to see whether conceptual understanding also improves in the transformed course and, if so, how students' views about and their understanding of measurement uncertainty are coupled.…”
Section: Resultsmentioning
confidence: 99%
“…We identified a set of learning goals with input from STEM faculty at CU as an early step of the transformation process. In addition to goals regarding measurement uncertainty [8,9] and scientific communication, more than one learning goal focused explicitly on views about experimental physics. Prior to the course transformation, we collected data from the original course for several semesters along dimensions aligned with these learning goals, in order to establish a baseline of comparison for the transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Our past work used the PMQ and the paradigm model to measure learning in an introductory physics lab course at the University of Colorado Boulder (CU) in Boulder, Colorado, US. Despite our context differing from that in which the PMQ was developed, we found that the PMQ nonetheless prompted responses from our students that could be analyzed using the point and set paradigms [16,17].…”
Section: Introductionmentioning
confidence: 86%